Hyperbaric oxygen therapy modulates serum OPG/RANKL in femoral head necrosis patients - Giuliano Vezzani; Silvia Quartesan; Pasqua Cancellara; Enrico Camporesi; Devanand Mangar; Thomas Bernasek; Prachiti Dalvi; Zhongjin Yang; Antonio Paoli; Alex Rizzato; Gerardo Bosco (Journal of Enzyme Inhibition and Medicinal Chemistry, 2017)
Hyperbaric oxygen therapy (HBOT) has beneficial effects on avascular necrosis of femoral head (ANFH), but its mechanism of action is still unclear. We investigated if HBOT upregulates serum osteoprotegerin (OPG) and/or inhibits osteoclast activation. 23 patients with unilateral ANFH at stage I, II and III consented to the study: the patients received standard HBOT. Serum OPG levels were obtained at the beginning of HBOT (T0), after 15 sessions (T1), 30 sessions (T2), after a 30-day break (T3), and after 60 sessions (T4). Magnetic resonance imaging (MRI) was obtained at T0 and about one year from the end of HBO treatments. Lesion size was compared between pre- and post-HBOT. 19 patients completed the study. HBOT reduced pain symptoms in all patients. HBOT significantly reduced lesion size in all stage I and II patients and in 2 of 11 stage III patients. HBOT increased serum OPG levels but receptor activator of nuclear factor kappa-B ligand (RANKL) levels did not change.